Audiovisual associations alter the perception of low-level visual motion - Kafaligonul, Hulusi; Oluk, Can (Frontiers in Integrative Neuroscience, 2015)
Motion perception is a pervasive nature of vision and is affected by both immediate pattern of sensory inputs and prior experiences acquired through associations. Recently, several studies reported that an association can be established quickly between directions of visual motion and static sounds of distinct frequencies. After the association is formed, sounds are able to change the perceived direction of visual motion. To determine whether such rapidly acquired audiovisual associations and their subsequent influences on visual motion perception are dependent on the involvement of higher-order attentive tracking mechanisms, we designed psychophysical experiments using regular and reverse-phi random dot motions isolating low-level pre-attentive motion processing. Our results show that an association between the directions of low-level visual motion and static sounds can be formed and this audiovisual association alters the subsequent perception of low-level visual motion. These findings support the view that audiovisual associations are not restricted to high-level attention based motion system and early-level visual motion processing has some potential role.